Analysis on the Impact of Large-Scale Sports Events on Regional Economy Based on SWOT-PEST Model - Lina Wang; Fanfei Zhao; Guanqun Zhang (Journal of Mathematics)
Against the background of surging globalization and accelerating urbanization, more and more cities are choosing to reposition their urban landscape by hosting sports events at different levels to achieve a great leap forward in urban development. Major sporting events can quickly gather various resources from all over the country and even the world for a city, promoting it to become a world-famous city with international influence. In the twenty-first century, more and more Chinese cities are bidding to host important sporting events at different levels, but historical experience shows that hosting slightly important sporting events is a “double-edged sword” and economic benefits are no longer the main reason for a city to host an event. Using the SWOT-PEST model, this paper provides an in-depth analysis of the advantages, disadvantages, opportunities, and challenges of marginally important sporting events of different levels affecting the regional economy from political, economic, social, and technological aspects, so as to understand in detail the economic impact of sporting events.